A statistical Study on Visitors to the Alwatan Laboratory Regarding Vitamin D Deficiency - Nabel Ahmed A Mansour (African Journal of Advanced Pure and Applied Sciences, 2025)
Vitamin D deficiency is widespread among both gender and in all age groups at increasing rates, and vitamin D deficiency is associated with low blood calcium levels and bone disorders in addition to systemic diseases (heart disease, cancer, etc.). This study was conducted under the supervision of the Alwatan Medical Clinic Laboratory located in the city of Hun in the municipality of Jafra during the period from 10/2024 to 12/2024. The focus was on the research problem, which is the problem related to vitamin D deficiency in different age groups. The aim was to identify vitamin D deficiency and provide a complete picture of the diagnosis, treatment mechanism, prevention, community awareness, and health awareness. The data were collected by a questionnaire to determine the percentage of vitamin D in both sexes and different age groups. An analysis was conducted on the samples taken and the results were read. The number of samples collected for different gender was 88 samples. The percentage of women was 77.3% and the percentage of men was 22.7%. The results showed that vitamin D deficiency is a common problem affecting different age groups, and the age groups between 2 and 60 years were the most vulnerable to vitamin deficiency, with the highest percentage being between 20 and 40 years, and the second place was occupied by the ages between 40 and 60 years. The prevalence was especially high among women and young people, which calls for effective health and awareness interventions.